Internal valve graft technique versus spreader graft/autospreader flap in functional rhinoplasty: A prospective cohort study - Yıldızdal, Süleyman; Altunal, Sinan Kadir; Koçer, Uğur (Acta Medica, 2026)
Objective: To compare a novel internal nasal valve graft technique with conventional spreader graft and autospreader flap methods in functional rhinoplasty, with respect to both functional and aesthetic outcomes. Materials and Methods: Forty patients undergoing primary rhinoplasty were prospectively enrolled and randomly allocated into two groups (n = 20 per group). Group 1 received a conventional spreader graft or autospreader flap, whereas Group 2 underwent the internal nasal valve graft technique, in which cartilage was positioned caudal to the conventional spreader graft line to augment the internal nasal valve without increasing dorsal width. Results: Preoperative dorsal widths and NOSE scores were comparable between the two groups. At 1-year follow-up, Group 1 demonstrated a statistically significant increase in dorsal width, whereas no significant change was observed in Group 2. NOSE scores improved significantly within both groups, with no statistically significant difference between the groups. Conclusion: The internal nasal valve graft technique provides functional improvement comparable to that of conventional methods while preventing dorsal widening, thereby representing an effective alternative in functional rhinoplasty that preserves the natural dorsal contour.